Triglyceride lowering in patients with different severities of hypertriglyceridaemia-associated acute pancreatitis: secondary analysis of a multicentre, prospective cohort study - Xiaoling Li; Lin Gao; Xiang Luo; Wenjian Mao; Lu Ke; Xiaoyan Lai; Lingyan Fu; Yaolu Liu (BMJ Open Gastroenterology)
Objective It is controversial whether rapid lowering of triglyceride (TG) levels is associated with clinical benefits in patients with hypertriglyceridaemia-associated acute pancreatitis (HTG-AP). In particular, patients with different severity of disease may respond differently to TG-lowering therapy. In this study, we aimed to explore the association between rapid decline in serum TG levels and organ failure in patients with different severities of HTG-AP.Methods This is a secondary analysis of data from a multicentre, prospective registry recruiting HTG-AP patients admitted within 72 hours from the onset of symptoms. Patients were dichotomised into either target reaching (TG≤5.65 mmol/L on study day 3) or not. The primary outcome was the presence of organ failure at day 14. The association between target-reaching and the primary outcome was modelled. Furthermore, subgroup analyses were conducted based on the disease severity of HTG-AP patients at enrolment.Results Overall, 413 patients were included for analysis, of whom 192 (46.5%) reached the target on day 3. For the overall study cohort, there was no significant difference in presence of organ failure at day 14 between patients reaching the target or not (3.1% vs 6.8%, p=0.091). In the subgroup of HTG-AP patients with organ failure at enrolment, compared with patients with TG>5.65 mmol/L on day 3, patients who reached the target had significantly lower presence of organ failure at day 14 (7.8% vs 22%, p=0.039) and lower incidence of infected pancreatic necrosis within 60 days (3.1% vs 11.9%, p=0.049). Similar findings were seen in the subgroup with more severe HTG-AP (APACHE II ≥8 at enrolment).Conclusion More rapid decline of serum TG levels was associated with decreased presence of organ failure at day 14 in patients with more severe HTG-AP.Trial registration number The Chinese Clinical Trial Registry, number ChiCTR2000039541.